2015
DOI: 10.1371/journal.pone.0124659
|View full text |Cite
|
Sign up to set email alerts
|

Attrition of TCR Vα7.2+ CD161++ MAIT Cells in HIV-Tuberculosis Co-Infection Is Associated with Elevated Levels of PD-1 Expression

Abstract: Mucosal-associated invariant T (MAIT) cells are evolutionarily conserved antimicrobial MR1-restricted CD8+ T cells co-expressing the semi-invariant TCR Vα7.2, and are numerous in the blood and mucosal tissues of humans. MAIT cells appear to undergo exhaustion in chronic viral infections. However, their role in human immunodeficiency virus type 1 (HIV-1) mono-infection and HIV/tuberculosis (TB) co-infection have seldom been elaborately investigated. We conducted a cross-sectional study to investigate the freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 35 publications
3
72
4
Order By: Relevance
“…Given multiple previous reports of peripheral blood MAIT cell loss in inflammatory disease models (2,(15)(16)(17)(18)(19)(20), we assessed circulating MAIT cell frequencies in healthy and SIVinfected RMs. Lower frequencies and absolute numbers of MAIT cells were detected in the peripheral blood of SIV-infected versus SIV-uninfected RMs ( Fig.…”
Section: Identification Of Mait Cells In Rhesus Macaque Peripheral Blmentioning
confidence: 99%
See 2 more Smart Citations
“…Given multiple previous reports of peripheral blood MAIT cell loss in inflammatory disease models (2,(15)(16)(17)(18)(19)(20), we assessed circulating MAIT cell frequencies in healthy and SIVinfected RMs. Lower frequencies and absolute numbers of MAIT cells were detected in the peripheral blood of SIV-infected versus SIV-uninfected RMs ( Fig.…”
Section: Identification Of Mait Cells In Rhesus Macaque Peripheral Blmentioning
confidence: 99%
“…ϩ MAIT cells in HIV-infected patients (17,18,20). The migration of MAIT cells to tissue sites of inflammation may therefore be impaired in the context of HIV/SIV infection.…”
Section: Identification Of Mait Cells In Rhesus Macaque Peripheral Blmentioning
confidence: 99%
See 1 more Smart Citation
“…CD8 + CCR6 + mucosal-associated invariant T cells in infected HIV patients tend to have lower surface CCR6 expression compared with healthy control mucosalassociated invariant T cells [56,57], possibly leading to their failure to migrate to key immunological sites.…”
Section: T H 17-like Cells and Precursorsmentioning
confidence: 99%
“…Multiple evidences support the potential association between CIA and T cell immunosenescence, although it still remains a conundrum as to whether TB plays a critical role in HIV disease progression. We recently showed that HIV/TB co-infection depleted the frequency of mucosal-associated invariant T cells (MAIT) with significant up-regulation of PD-1 [16]. Therefore, the possible role of TB on premature senescence and CIA in HIV disease remains largely elusive.…”
Section: Introductionmentioning
confidence: 99%